Economic theory and latin america external debt (1994)
This article reviews the concepts involved in the problem of foreign debt. From a Monetary Keynesian approach, it analyzes the differences and similarities between the Kindleberger model, the German Marxist view, the orthodox theory of debt cycles held by the World Bank and Latin American structuralism. Finally, there are some elements of German Monetary Keynesianism in an integration of financial factors and growing microeconomic concern for insti tutions. In the practical field there is a consideration of the policies required to solve the debt problem which each school of thought would recommend. The author supports the thesis of Riese, founder of the Berlin School: in view of their limi ted monetary and productive potential, developing countries are unable to counter the devaluation strategies of the leading industrial countries... the strategies of devaluation of the underdeveloped countries and the consolidation of the balance of payments as the ruling monetary policy, much promoted by recent academic literature, are doomed to fail.